KEBERADAAN FUNGI MIKORIZA ARBUSKULA (FMA) PADA TEGAKAN KEMIRI ALEURITES MOLUCCANA WILLD DI DESA BENTUNAI KABUPATEN SAMBAS - feri, .; burhanuddin, .; herawatiningsih, ratna (JURNAL HUTAN LESTARI, 2016)
Aleurites molucanna Will is a vegetable oil that has the potential to be used as raw materials for petroleum substitutes. Before the use of A. molucanna Will on a large scale is needed seeds that have good growth potential by using of Arbuscular Mycorriza Fungi (AMF). The study, entitled presence in the stands of A.Molucanna Arbuscular Mycorriza Fungi (AMF) aims to prove a link between the FMA with A.Molucanna and obtain other types of AMF associated with pecans. The research was conducted from March to May 2016 in the silviculture laboratory and field. Soil and root samples were taken in the Bentunai village and the survey method purposively at three levels A.Molucann. The research proves there is association between the Arbuscular Mycorriza Fungi (AMF) with hazelnut attested by their spores in a number of 455 spores / 100 g soil is composed of 8 types of spores belonging to the genus Glomus and the presence of infection at the root of the whole roots of the observed average rate of infection classified as 3 classification class (medium) Keywords: Bentunai, Existence, Kemiri, Mycorrhizae, Sambas.